2019
DOI: 10.1097/md.0000000000014484
|View full text |Cite
|
Sign up to set email alerts
|

Submucosal 1-tunnel endoscopic resection for treating upper gastrointestinal multiple submucosal tumor originating from the muscularis propria layer

Abstract: To explore the feasibility and efficacy of submucosal 1-tunnel endoscopic resection (1-tunnel STER) for the treatment of multiple upper gastrointestinal submucosal tumors (GI-SMTs) originating from the muscularis propria (MP) layer. A total of 12 patients with multiple upper GI-SMTs (no less than 2 SMTs) who underwent 1-tunnel STER from April 2013 to October 2017 were included. Clinical data on general characteristics, operation-related parameters, adverse events, and follow-up results were recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…A recent meta-analysis on STER demonstrated an en bloc resection rate of 94.9%, with overall gas-related and inflammation-related adverse events rates of 21.5% and 8.4%, respectively, a postinterventional bleeding rate of 2.2%, and length of hospital stay of a median of 3.8 days [26]. Wang et al published excellent outcomes with the STER procedure by successfully removing multiple leiomyomas with a mean diameter of 15 mm in 12 patients [27]. In a prospective, comparative study with 66 patients, STER and VATS were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis on STER demonstrated an en bloc resection rate of 94.9%, with overall gas-related and inflammation-related adverse events rates of 21.5% and 8.4%, respectively, a postinterventional bleeding rate of 2.2%, and length of hospital stay of a median of 3.8 days [26]. Wang et al published excellent outcomes with the STER procedure by successfully removing multiple leiomyomas with a mean diameter of 15 mm in 12 patients [27]. In a prospective, comparative study with 66 patients, STER and VATS were investigated.…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 , 20 ] Furthermore, several studies revealed that endoscopy could achieve en bloc resection in case of esophageal GISTs, and endoscopic resection is safe, effective, and minimally invasive. [ 2 , 8 , 21 , 22 ] Moreover, several lymphomas presented as SELs and treated with endoscopic resection have been reported. [ 23 27 ] In addition, according to the literature review, some other rare cases were treated with endoscopy, similar to follicular dendritic cell sarcoma and adenoid cystic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…During the surgery, the tumor must be excised from the submucosa or inner muscle layer along the external edge of the tumor, and the capsule of the tumor must remain intact. STER technology is close to endoscopic myotomy (POEM) (33), which involves a tunnel to treat multiple lesions (34). However, the space inside of the tunnel is limited, and the operation and removal of large lesions are difficult.…”
Section: Discussionmentioning
confidence: 99%